Common Sun Skink Eutropis multifasciata (Kuhl 1820) sold for Traditional Medicine in Indonesia and potential conservation implications. - Janssen, Jordi; Gomez, Lalita (Ethnobiology and Conservation, 2019)
Reptiles are one of the most frequently encountered animal species in the trade for traditional medicine. The use of reptiles for medicinal purposes has been documented throughout the world, impacting dozens of species. Despite the broad occurrence of reptiles in medicinal trade, there is a general lack of information concerning the scale or impact of this trade and the species involved. Here we report the sale of Common Sun Skinks Eutropis multifasciata on the island of Java in Indonesia. We surveyed 13 wildlife markets and three reptile pet stores in eight cities across Java, documenting 110 Common Sun Skinks in trade in six markets in five cities. This skink is sold for traditional medicinal purposes with several vendors stating its use to treat skin problems like “itchiness”. This particular use has not been well documented in Indonesia. Further, the Common Sun Skinks were primarily sold by vendors selling Tokay Geckos for a similar purpose. This is of potential conservation concern as Tokay Geckos are harvested en masse for medicinal purposes which has resulted in significant population declines, and this could lead to potential over¬exploitation of the Common Sun Skink in response to this decline.